IMPLEMENTASI MEDIA OBJEK LANGSUNG DALAM PEMBELAJARAN MENULIS PUISI - Alvina Nurzakia; Albertus Sinaga; Hilman Yusra (Universitas Negeri Makassar, 2023)
Implementation of Direct Object Media in Poetry Writing Learning. This study aims to determine the implementation of direct media objects in learning to write poetry in class VIII of SMP Islam Al Falah Jambi. The researcher used a qualitative approach, with data collection methods in the form of observation, interviews with class VIII Indonesian teachers, and backups. Data analysis techniques were carried out by collecting, reducing, presenting, and concluding. The results of the research show that the medial implementation of direct objects is carried out effectively. Stages of learning through direct object media, namely the planning stage of preparing direct object media and preparing learning materials. Then comes the implementation stage of learning with medial objects Students directly observe objects outside the classroom and are divided into several groups, Students begin to observe predetermined objects and start writing poetry, and then the results of their writing are collected. Finally, the teacher's evaluation stage assesses the results of the students' poetry.